Simultaneous Pheochromocytoma, Paraganglioma, and Papillary Thyroid Carcinoma without Known Mutation - Lorena Rasquin; Janna Prater; Jane Mayrin; Corrado Minimo (Case Reports in Endocrinology)
Background. Pheochromocytoma/paraganglioma is a rare tumor from neuroendocrine cells. 1/3rd of cases have germline mutations. Papillary thyroid carcinoma (PTC) is a common neoplasm from follicular cells of the thyroid. We report a case of pheochromocytoma/paraganglioma and PTC with negative testing for common mutations. Case. 32-year-old male with incidental liver mass during laparoscopy for acute appendicitis. His symptoms included abdominal pain and profuse axillary hyperhidrosis. MRI showed an 11x12x14 cm cystic and solid mass in right adrenal gland, and 3.4x2.9x3.8 cm mass in porta hepatis. Urine metanephrines was elevated. After preoperative alpha-blockade, patient underwent total right adrenalectomy. Pathology report confirmed diagnosis of pheochromocytoma. According to the Grading system for Adrenal Pheochromocytoma and Paraganglioma (GAPP), tumor’s score was 9, indicating poorly differentiated tumor. Ki67 index 5% and S100 were negative. Postoperatively, plasma free metanephrines normalized but plasma free normetanephrines remained elevated. Based on this biochemical profile, presence of paraganglioma was suspected. CT showed 4.2x3.5 cm round soft tissue mass in porta hepatis which increased in size from previous MRI. Simultaneously, PET scan identified a 1.5 cm thyroid mass. Calcitonin level was normal. Fine-needle aspiration was consistent with PTC. Resection of the mass and total thyroidectomy were performed with confirmation of paraganglioma S100 positive and PTC. Normetanephrines decreased to 283 (<148 pg/mL); free metanephrines remained normal. Gene mutation of EGLN1, FH, KIF1B, MEN1, NF1, RET, SDHAF2, SDHC, SDHD, TMEM127, VHL, and SDHA was negative. Conclusion. Whether paraganglioma/pheochromocytoma/PTC combination is coincidental or resulted from an underlying unknown mutation cannot be excluded.